2011
DOI: 10.1016/j.jeurceramsoc.2010.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of biomorphic SiC ceramics and SiC/Si composites fabricated from medium density fiberboard

Abstract: A study has been made of the dependences of the electrical resistivity and the Hall coefficient on the temperature in the range 1.8-1300 K and on magnetic fields of up to 28 kOe for the biomorphic SiC/Si (MDF-SiC/Si) composite and biomorphic porous SiC (MDF-SiC) based upon artificial cellulosic precursor (MDF -medium density fiberboards). It has been shown that electric transport in MDF-SiC is effected by carriers of n-type with a high concentration of ∼1020 cm−3 and a low mobility of ∼0.4 cm2 V−1 s−1. The spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
8
0
1
Order By: Relevance
“…At temperatures above 800°C, the sintered SiC resistivity became comparable with the CMC data. The resistivity of biomorphic SiC closely matched the Sylramic‐iBN fibers up to approximately 600°C . Beyond that temperature, the biomorphic SiC did not decrease in resistivity as much as the model estimated for the fibers.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…At temperatures above 800°C, the sintered SiC resistivity became comparable with the CMC data. The resistivity of biomorphic SiC closely matched the Sylramic‐iBN fibers up to approximately 600°C . Beyond that temperature, the biomorphic SiC did not decrease in resistivity as much as the model estimated for the fibers.…”
Section: Discussionsupporting
confidence: 53%
“…The ratio of ρ/ρ o (fiber resistivity relative to the initial resistivity at 25°C) was assumed to be exponential based on literature data for chemical vapor infiltrated (CVI) SiC composites with Sylramic‐iBN fibers, sintered SiC, biomorphic SiC, and Hi‐Nicalon fibers (all of which are shown in Figure ). Note that the experimental data from CVI SiC/SiC and this study were both obtained under non‐isothermal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It can be observed that the increment of complex permittivity with the increasing temperatures is mainly caused by the relaxation loss and conductance loss. For the SiC materials, electron relaxation polarization would be the dominant polarization mechanism and response to the electromagnetic field at high temperatures due to the thermal excitation of SiC materials [37,38]. Arrhenius formula could be used to describe the relationship between relaxation time and temperature under this condition [39]:…”
Section: Dielectric Properties Of Sic F /Sic Composites At High Tempementioning
confidence: 99%
“…It can be observed that the increase of complex permittivity is mainly induced by the relaxation polarization and conductance loss at high temperatures [38]. In the SiC materials, electron relaxation polarization would be the dominant polarization mechanism and response to the electromagnetic field at high temperatures due to the thermal excitation of SiC materials [39,40]. We can use Arrhenius formula to describe the relationship between relaxation time and temperature under this condition [41]:…”
Section: Dielectric Properties Of Sic F /Sic-al 2 O 3 Composites At Hmentioning
confidence: 99%